2006
DOI: 10.2337/dc06-0057
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, Obesity, and Risk of Type 2 Diabetes in Women

Abstract: OBJECTIVE -To examine ethnic differences in risk of type 2 diabetes, taking dietary and lifestyle risk factors into account. -A prospective (1980 -2000) cohort (from The Nurses' Health Study) including 78,419 apparently healthy women (75,584 whites, 801 Asians, 613 Hispanics, and 1,421 blacks) was studied. Detailed dietary and lifestyle information for each participant was repeatedly collected every 4 years. CONCLUSIONS -The risk of diabetes is significantly higher among Asians, Hispanics, and blacks than amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
283
4
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 420 publications
(322 citation statements)
references
References 31 publications
25
283
4
5
Order By: Relevance
“…The data collected on smoking, physical activity, and diet from the self‐administered questionnaires may be subject to recall bias. Future modifications of the LS7 metrics could make BMI specific for each racial/ethnic group because some studies have demonstrated that Asians are at a higher risk of weight‐related diseases, such as CVDs, at lower BMIs 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…The data collected on smoking, physical activity, and diet from the self‐administered questionnaires may be subject to recall bias. Future modifications of the LS7 metrics could make BMI specific for each racial/ethnic group because some studies have demonstrated that Asians are at a higher risk of weight‐related diseases, such as CVDs, at lower BMIs 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, BMI has been used to define overweight and obesity, and is predictive of cardiometabolic risk including incident type 2 diabetes [6] and cardiovascular events such as myocardial infarction [7]. However, BMI has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a large international casecontrol study, measures of abdominal obesity (waist circumference and WHR) were more strongly associated with myocardial infarction than BMI [7]. Second, BMI may not be appropriate to use in all individuals, as the association of BMI with cardiometabolic risk seems to vary according to sex [9,10] and ethnicity [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional diabetes incidence rates predicted by the Hill equation, and accuracy of diabetes prevalence predicted using NHANES incidence rate estimates versus prevalence predicted using the rate estimates obtained from the Hill equation women, compared with the observed rates in Shai et al [20]. The model predicted the 20-year diabetes risk of middle-aged, overweight (144 vs. 140 per 1000) and obese (270 vs. 306 per 1000) middle-aged Swedish men with reasonable accuracy [21].…”
Section: Tablementioning
confidence: 99%
“…Similarly, total diabetes incidence pertaining to middle-aged (average age, 45 years) Caucasian, Asian, Hispanic, and Black women (baseline average BMI of 24.3, 22.7, 24.3, and 26.0, respectively) during the next 20 years were predicted using the model, and compared with observed incidence values from a long-term (1980e2000) female cohort in the United States [20]. Further, the incidence rates predicted for normal weight, overweight, and obese middle-aged men (average age, 50 years) were compared with the observed rates from a longterm (20 years) Swedish cohort study reported by Arnlov et al [21].…”
Section: Comparison Of Model Predictions With Literature Datamentioning
confidence: 99%